Pengaruh Citra Merek, Harga, Promosi dan Electronic Word of Mouth Terhadap Keputusan Pembelian Produk Bedak Padat Wardah Pada PT Pargon Tecnology and Inovation (Studi Kasus Mahasiswa Fakultas Ekonomi STIE Graha Karya Muara Bulian) - Irfan Widyanto; Albetris Albetris (Universitas Batanghari, 2021)
The first study aims to analyze the Effect of Brand Image, Price, Promotion and Electronic Word of Mouth on Wardah Solid Powder Product Purchase Decisions at the Faculty of Economics STIE Graha Karya Muara Bulian Jambi simultaneously and the second is to determine the effect of Brand Image, Price, Promotion and Electronic Word of Mouth on Wardah Solid Powder Product Purchase Decisions at the Faculty of Economics STIE Graha Karya Muara Bulian Jambi Partially. The research methodology used is, the researcher uses a design using descriptive methods and quantitative methods. The data used are secondary data and primary data. The population in this study were 150 economic students at STIE Graha Karya Muara Bulian Jambi. The sample in this study was 60 respondents to the students of the Faculty of Economics STIE Graha Karya Muara Bulian Jambi. The results of multiple linear regression obtained Y = - 0.386 + 0.667 X1 + 0.221 X2 + 0.458 X3 - 0.163 X4 + e, Based on the coefficient of determination it can be seen that brand image, Price, Promotion and Electronic Word of Mouth have an effect on purchase decisions amounted to 75.6%, while the remaining 24.4% is influenced by other variables. Based on the results of the f test regression, it can be seen that the value of f count is 42.71> f table 2.54, which means brand image, price, promotion and electronic word of mouth have a positive and significant effect on purchasing decisions.